Capacity Development Strategy for Manufacturing MSMEs in Bogor Regency - Ramadhany, Oemmy; Sutrisno, Edy (Yayasan Sinergi Kawula Muda, 2025)
This study aims to analyze capacity development strategies for Micro, Small, and Medium Enterprises (MSMEs) in the manufacturing sector of Bogor Regency. Despite their significant contribution to the region’s Gross Regional Domestic Product (GRDP), the quantitative growth of MSMEs has not aligned with improvements in competitiveness and business sustainability. Adopting a descriptive qualitative approach, this research collected data through in-depth interviews with nine stakeholder groups and a review of policy documents and sectoral statistics. Referencing the capacity development framework from the United Nations Development Programme (UNDP) and Horton’s three-tiered intervention model, the study identifies five key challenges in MSME capacity strengthening: weak stakeholder coordination, internal capacity gaps among business actors, non-contextual policy responses, disparities in program implementation, and the absence of outcome-based evaluation systems. The results suggest that capacity development must be carried out simultaneously at the micro level (entrepreneurs), meso level (supporting organizations), and macro level (policy and systems), with emphasis on data integration, actor segmentation, and outcome-based evaluation. The study contributes theoretically by contextualizing international frameworks to local governance and practically by proposing a classification-based strategy and behavior-sensitive evaluation model for MSME development. The results offer actionable insights for designing inclusive and adaptive capacity-building policies at the subnational level.